De lof der hypocrisie - Van Alsenoy, Jan (Antwerpen : Ontwikkeling, 1956)
Bibliotheek Camille Huysmans
Dedicator: Van Alsenoy, Jan, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: maatschappijkritiek